2022
DOI: 10.3389/fendo.2022.915309
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Testosterone Predicts Body Composition and Metabolic Response to Testosterone Therapy

Abstract: ContextMale hypogonadism adversely affects body composition, bone mineral density (BMD), and metabolic health. A previous report showed that pre-treatment testosterone (T) levels of <200 ng/dl is associated with greater improvement in spine BMD with T therapy. However, to date, there is no study that investigates whether baseline T levels also influence body composition and metabolic response to T therapy.ObjectiveThe aim of this study is to determine if there are differences in the changes in body comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Apart from the myogenic machinery, Gao et al., further reported that osteoblast differentiation was activated by T therapy in MC3T3-E1 cells through ERK-1/2, activated Runx2 pathway ( 156 ). Changes in body composition and bone density with T therapy from our lab and other investigators support the above findings from in-vitro and animal studies ( 146 , 157 , 158 ). Hence, we hypothesize that the reciprocal effect of T therapy on fat mass, lean mass and bone mass is due to the shift in lineage differentiation from adipogenesis to both myogenesis and osteogenesis.…”
Section: Emerging Therapeutic Treatment In Bone Loss Of Obese and T2d...supporting
confidence: 85%
See 1 more Smart Citation
“…Apart from the myogenic machinery, Gao et al., further reported that osteoblast differentiation was activated by T therapy in MC3T3-E1 cells through ERK-1/2, activated Runx2 pathway ( 156 ). Changes in body composition and bone density with T therapy from our lab and other investigators support the above findings from in-vitro and animal studies ( 146 , 157 , 158 ). Hence, we hypothesize that the reciprocal effect of T therapy on fat mass, lean mass and bone mass is due to the shift in lineage differentiation from adipogenesis to both myogenesis and osteogenesis.…”
Section: Emerging Therapeutic Treatment In Bone Loss Of Obese and T2d...supporting
confidence: 85%
“…Pgc1a on the adipogenic/myogenic cascade need to be explored. We hypothesize that T therapy activates the trio cascade PPARγ-Prdm16-Pgc1a leading to initiation of the switch from adipogenesis to myogenesis along with promotion of osteogenesis ( Figure 2 ) responsible for the observed positive effect on fat mass, lean mass and bone mass in hypogonadal men ( 146 , 157 , 158 ). The Endocrine Society has suggested the use of T to maintain or prevent loss of lean mass in men with HIV ( 159 ).…”
Section: Emerging Therapeutic Treatment In Bone Loss Of Obese and T2d...mentioning
confidence: 99%
“…Nitric oxide is necessary for maintaining and sustaining physiological oxygenation during the critical windows of cellular regeneration–rejuvenation and the timing hypothesis of hormone therapy. Physiological concentrations of testosterone significantly increased nitric oxide production ( Campelo et al, 2012 ), and baseline testosterone levels predict body composition and metabolic response to TRT ( Deepika et al, 2022 ) and support the prostate safety of TRT in newly diagnosed men with hypogonadism ( Debruyne et al, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…In all the meta-analyses, TRT exerts a similar, positive effect in reducing fat mass and in increasing muscle mass, without changing body mass index (BMI) or weight [37,43,44]. A positive effect on fasting glycemia was also apparent, whereas a reduction in total cholesterol and triglycerides were evident in some, but not all, the meta-analyses [37].…”
Section: Trt and Body Composition And Glycolipid Metabolismmentioning
confidence: 93%